AB0783 Medical costs associated with rheumatoid arthritis in turkey: an analysis of real-world data. (23rd January 2014) - Baser, O.; Burkan, A.; Baser, E.; Koselerli, R.; Ertugay, E.; Altinbas, A.
Abstract : Background: Health Transformation Programme implementation by the Turkish Ministry of Health resulted in significant health system changes in Turkey. 1 Recognizing the importance of information technology and health technology assessment, Turkey invested in stronger systems and data collection. MEDULA, a nationwide integrated system between health insurance and healthcare providers, was built to collect e-invoice information electronically in 2007. Rheumatoid arthritis (RA) costs in Turkey were analyzed for the first time using real-world data. Objectives: Estimate and identify medical cost determinants associated with RA in Turkey using nationwide real-world data. Methods: Data was obtained from MEDULA (2009-2011). Adult RA patients (ages 18-99) were identified (01JUN2010-31DEC2010), and were required to have two RA diagnoses ≥60 days apart, and were grouped as prevalent and incident cases. The first RA claim date was designated as the index date. Healthcare costs were examined following the index date. Descriptive and multivariate analyses are provided. Pharmacy, outpatient and inpatient claims were compiled. Generalized linear models were used to calculate expected annual costs after controlling for age, gender, region, comorbid conditions and medication. Results: A total of 2, 613 patients met all inclusion criteria (693 incident; 1, 920 prevalent patients). Prevalent patients were older, less likely to reside in the Marmara region, had higher comorbidity index scores and were more likely to be prescribed non-steroidal anti-inflammatory drugs, biologics and disease-modifying anti-rheumatic drugs relative to incident patients. Average annual costs were €2, 000 (incident) and €2, 386 (prevalent), due to pharmacy costs (73%, incident; 60%, prevalent). For both groups, inpatient and outpatient costs were mostly due to physician costs. Costs did not significantly differ in terms of age or region, prior comorbid conditions and medication use significantly affected cost estimation. Image/graph: Conclusions: RA annual costs were found to be lower in Turkey relative to estimates in Europe, yet a significant portion was due to pharmacy costs. Comparative effectiveness analyses may be useful to decrease RA pharmacy costs. References: Akdag R. Progress Report 2008 Health Transformation Programme: Ministry of Health, Ankara; 2008. Disclosure of Interest: None Declared